PENGARUH PEMAHAMAN, SANKSI PERPAJAKAN, TINGKAT KEPERCAYAAN PADA PEMERINTAH DAN HUKUM, SERTA NASIONALISME TERHADAP 22 KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PBB-P2 (Studi Pada Wajib Pajak PBB-P2 di Kota Banjar) - Purnamasari, Apriani; Pratiwi, Umi; Sukirman, Sukirman (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2017)
The main purpose of this research is to examine the effect of perceived tax understanding, tax penalties, trust in government and law, and nationalism towards taxpayer compliance in paying property tax. Using Slovin formula, 100 respondents were selected as representative sample from the tax payers in Banjar, Indonesia. Data were collected using closed questionnaire and analyzed by multiple linear regression. The results showed that the understanding of tax regulation, tax penalties, and nationalism had significantly positive effect. However, trust in goverment and the law did not significantly affect taxpayerÂ compliance in paying property tax.